Morphology evolution regulation of dual-doped S, Fe-NiMoO4 microrods based on precipitation-dissolution equilibrium for oxygen evolution. (15th March 2023) - Li, Meng-Xuan; Xiao, Bo; Zhao, Zi-Yi; Ma, Yu; Zhou, Ya-Nan; Zhang, Xin-Yu; Wang, Feng-Ge; Chai, Yong-Ming; Dong, Bin
Graphical abstract: Highlights: Trace of S, Fe dual-doping is realized by precipitation dissolution equilibrium. Two-step rational construction of S, Fe-NiMoO4 @IF 1D microrods is proposed. FeS prevent the contact between IF surface and Ni 2+ ions to produce NiFe-LDH. DFT reveals that S, Fe dual-doping modulates the electronic structure and Gibbs free energy. Abstract: Structurally and componentially controlled non-precious metal-based catalysts for oxygen evolution reaction (OER) have been identified as an effective way to achieve green water electrolysis. Herein, a simple route for anion-cation dual-doping is introduced to generate S, Fe dual-doped NiMoO4 one-dimensional microrods by exploiting a novel precipitation-dissolution equilibrium during the hydrothermal process. A precipitation-dissolution equilibrium of FeS on the surface of iron foam (IF) is introduced to release trace and constant amount of sulfur and iron ions, which not only regulate the morphology evolution of NiMoO4 microrods through hindering the formation of NiFe-LDH, but also realize uniformly S, Fe dual-doped NiMoO4 microrods. The optimized S, Fe-NiMoO4 @IF ensures the abundance of active sites as well as fast charge transfer rates. Meanwhile, excellent OER performance of S, Fe-NiMoO4 @IF have been obtained, requiring a low overpotential of 235.3 mV at 100 mA cm −2 and a small Tafel slope of 40 mV dec -1, coupled with a good long-term stability. The density functional theory (DFT) reveals that S, Fe dual-doping can improve the electronic transfer rate of the reaction intermediates and reduce the Gibbs free energy. This work provides a new simple anion-cation dual-doped strategy for the development of high-performance, morphology-controlled catalysts.